LAND USE AND LAND CADASTRAL MANAGEMENT WORKS - Nurali Shermatovich Umarov; Gulmurodov Farrukh Eshmurodovich; Polatov Asliddin Sayfullayevich; Akhmedov Abdulatif Bakhtiyor’s son (Zeta Repository, 2023)
The article shows the need to create a database by using GAT programs in the organization and management of state land cadastre works, to create new electronic digital cards, and to develop methods for creating land cadastral cards and conduct them based on established principles. Also, information on the scientific results of the CIS scientists on the organization and management of state land cadastre work, land construction, design and land monitoring was given.